Estimating the effect of nutritional interventions using observational data: the American Heart Association's 2020 Dietary Goals and mortality. Issue 2 (27th May 2021) - Chiu, Yu-Han; Chavarro, Jorge E; Dickerman, Barbra A; Manson, JoAnn E; Mukamal, Kenneth J; Rexrode, Kathryn M; Rimm, Eric B; Hernán, Miguel A
ABSTRACT: Background: Because randomized trials of sustained dietary changes are sometimes impractical for long-term outcomes, the explicit emulation of a (hypothetical) target trial using observational data may be an important tool for nutritional epidemiology. Objectives: We describe a methodological approach that aims to emulate a target trial of dietary interventions sustained over many years using data from observational cohort studies. Methods: We estimated the 20-y risk of all-cause mortality under the sustained implementation of the food-based goals of the American Heart Association (AHA) 2020 using data from 3 prospective observational studies of US men [Health Professionals Follow-up Study (HPFS)] and women [Nurses' Health Study (NHS) and Nurses' Health Study II (NHS II)]. We applied the parametric g-formula to estimate the 20-y mortality risk under a dietary intervention and under no dietary intervention. Results: There were 165, 411 participants who met the eligibility criteria. The mean age at baseline was 57.4 y (range, 43–82 y) in the HPFS, 52.4 y (range, 39–66 y) in the NHS, and 40.2 y (range, 30–50 y) in the NHS II. During 20 y of follow-up, 13, 241 participants died. The estimated 20-y mortality risks under a dietary intervention versus no intervention were 21.9% compared with 25.8%, respectively, in the HPFS (risk difference, −3.9%; 95% CI: −4.9% to −3.2%); 10.0% compared with 12.6%, respectively, in the NHS (risk difference, −2.6%; 95% CI: −3.1% to −1.8%); and 2.1% compared with 2.5%, respectively, in the NHS II (risk difference, −0.35%; 95% CI: −0.56% to −0.09%). The corresponding risk ratios were 0.85 (95% CI: 0.81–0.88) in the HPFS, 0.79 (95% CI: 0.75–0.85) in the NHS, and 0.86 (95% CI: 0.78–0.96) in the NHS II. Conclusions: We estimated that adherence to the food-based AHA 2020 Dietary Goals starting in midlife may reduce the 20-y risk of mortality.